Sodium vanadium fluorophosphate and preparation method and application of carbon-coated sodium vanadium fluorophosphate
By adjusting the element molar ratio and carbon coating technology, the problems of the heterogeneous phases in vanadium fluorine phosphate are solved, their purity and performance are improved, the energy density and cycle life of the battery are improved, and they are suitable for industrial production.
Patent Information
- Application Number
- CN202310710026.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-14
Smart Images

Figure CN119143103A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a preparation method of sodium vanadium fluorophosphate and carbon-coated sodium vanadium fluorophosphate and applications thereof. Background Art
[0002] Sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVOPF) is a typical sodium superion conductor (NASICON) with advantages such as stable three-dimensional framework structure, high theoretical specific capacity (128mAh / g) and high operating voltage, and has become a hot spot in the research of sodium ion battery electrode materials. However, the currently prepared sodium vanadium fluorophosphate contains impurities such as sodium vanadium phosphate (Na3V2(PO4)3), which directly reduces its discharge specific capacity and operating voltage, and then reduces the energy density of the battery. Therefore, it is necessary to improve the preparation method of sodium vanadium fluorophosphate to obtain sodium vanadium fluorophosphate with high purity and excellent performance. Summary of the invention
[0003] In view of this, the present application provides a preparation method of sodium vanadium fluorophosphate and carbon-coated sodium vanadium fluorophosphate and its application. The preparation method provided in the present application can reduce the generation of impurities such as sodium vanadium phosphate and improve the purity of sodium vanadium fluorophosphate, thereby obtaining sodium vanadium fluorophosphate with excellent performance, which is beneficial to its use.
[0004] In a first aspect, the present application provides a method for preparing sodium vanadium fluorophosphate, comprising:
[0005] A sodium source, a vanadium source, a phosphorus source and a fluorine source are mixed to form a first raw material, wherein the molar ratio of sodium element, vanadium element, phosphorus element and fluorine element in the first raw material is a:b:c:d, wherein a, b, c, d are real numbers greater than 0, and a, b, c, d satisfy: when a / c≤1.5, a / b<1.5, a / d<1, or when a / c≥1.5, c / b<1, c / d<2 / 3;
[0006] The first raw material is processed to obtain a first precursor;
[0007] The first precursor is dried and calcined to obtain sodium vanadium fluorophosphate.
[0008] Optionally, when a / c≤1.5, 1.36<a / b<1.5, 0.83<a / d<1, or when a / c≥1.5, 0.89<c / b<1, 0.55<c / d<2 / 3.
[0009] Optionally, when a / c≤1.5, b is 2a / 3+e, d is a+3e, e>0, or when a / c≥1.5, b is c+f, d is 1.5c+3f, f>0.
[0010] Furthermore, when a / c≤1.5, 2.5≤a≤3.5, 0.1≤e≤0.2, or when a / c≥1.5, 1.6<c<2.4, 0.1≤f≤0.2.
[0011] Furthermore, when a / c≤1.5, 12.5≤a / e≤35, or when a / c≥1.5, 8.3<c / f<23.4.
[0012] Optionally, the first raw material is processed to obtain a first precursor, including: the first raw material is processed by at least one of a solid phase method, a hydrothermal method, a sol-gel method and a spray drying method to obtain the first precursor.
[0013] Optionally, the drying comprises treating at 100° C.-120° C. for 1 h-3 h.
[0014] Optionally, the calcination includes treating at 300°C-400°C for 1h-5h, and then treating at 600°C-800°C for 10min-10h.
[0015] In the preparation method of sodium vanadium fluorophosphate provided in the present application, the molar ratio of sodium, vanadium, phosphorus and fluorine is controlled to reduce the content of impurities in sodium vanadium fluorophosphate, thereby obtaining sodium vanadium fluorophosphate with high purity and excellent performance; and the preparation method is simple to operate, short in preparation process and high in preparation efficiency, which is conducive to the industrial production of sodium vanadium fluorophosphate and facilitates the use of sodium vanadium fluorophosphate.
[0016] In a second aspect, the present application provides a method for preparing carbon-coated sodium vanadium fluorophosphate, comprising:
[0017] A sodium source, a vanadium source, a phosphorus source, a fluorine source and a carbon source are mixed to form a second raw material, wherein the molar ratio of the sodium element, the vanadium element, the phosphorus element and the fluorine element in the second raw material is a':b':c':d', wherein a', b', c', d' are real numbers greater than 0, and a', b', c', d' satisfy: when a' / c'≤1.5, a' / b'<1.5, a' / d'<1, or when a' / c'≥1.5, c' / b'<1, c' / d'<2 / 3;
[0018] The second raw material is processed to obtain a second precursor;
[0019] The second precursor is dried and calcined to obtain carbon-coated sodium vanadium fluorophosphate.
[0020] In the preparation method of carbon-coated sodium vanadium fluorophosphate provided in the present application, the molar ratio of sodium, vanadium, phosphorus and fluorine is controlled to reduce the content of impurities in the sodium vanadium fluorophosphate, and the carbon coating can also improve the conductivity of the sodium vanadium fluorophosphate, thereby obtaining a material with high purity and excellent performance; and the preparation method is simple to operate, short in preparation process and high in preparation efficiency, which is conducive to the industrial production of carbon-coated sodium vanadium fluorophosphate and facilitates the use of carbon-coated sodium vanadium fluorophosphate.
[0021] In a third aspect, the present application provides a battery electrode, comprising at least one of sodium vanadium fluorophosphate produced by the preparation method described in the first aspect and carbon-coated sodium vanadium fluorophosphate produced by the preparation method described in the second aspect.
[0022] The battery pole pieces provided in the present application use sodium vanadium fluorophosphate and / or carbon-coated sodium vanadium fluorophosphate with high purity and excellent performance, which can improve the specific capacity and energy density of the battery pole pieces and facilitate the use of the battery pole pieces.
[0023] In a fourth aspect, the present application provides a battery, comprising the battery electrode described in the third aspect.
[0024] The battery electrode in the battery provided in the present application has high specific capacity and energy density, so that the battery has excellent electrochemical properties, which is beneficial to its use.
[0025] In a fifth aspect, the present application provides an electrical device comprising the battery described in the fourth aspect.
[0026] The electrical equipment provided in this application has excellent performance and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0028] Figure 1 This is a flow chart of a method for preparing sodium vanadium fluorophosphate provided in one embodiment of the present application.
[0029] Figure 2 This is a flow chart of a method for preparing carbon-coated sodium vanadium fluorophosphate provided in one embodiment of the present application.
[0030] Figure 3 A schematic cross-sectional view of a positive electrode provided in one embodiment of the present application.
[0031] Figure 4 This is the XRD spectrum of Na3V2(PO4)2F3@C prepared in Examples 1-4 and Comparative Example 1.
[0032] Figure 5 TG curves of Na3V2(PO4)2F3@C prepared in Examples 1-4 and Comparative Example 1.
[0033] Figure 6 This is the SEM image of Na3V2(PO4)2F3@C prepared in Examples 1-4 and Comparative Example 1.
[0034] Figure 7 The charge and discharge curves of the battery made of Na3V2(PO4)2F3@C prepared in Examples 1, 3 and 4 under 0.2C conditions.
[0035] Figure 8 The charge and discharge curves of the battery made of Na3V2(PO4)2F3@C prepared in Example 2 and Comparative Example 1 under 0.2C conditions.
[0036] Fig. 9 This is a cycle performance curve of the battery made of Na3V2(PO4)2F3@C of Examples 1-4 and Comparative Example 1 under 1C conditions.
[0037] Fig.10 This is a rate performance curve of the battery made of Na3V2(PO4)2F3@C of Examples 1-4 and Comparative Example 1. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0039] See also Figure 1 , is a flow chart of a method for preparing sodium vanadium fluorophosphate provided in one embodiment of the present application, comprising:
[0040] S101: A sodium source, a vanadium source, a phosphorus source and a fluorine source are mixed to form a first raw material, wherein the molar ratio of sodium element, vanadium element, phosphorus element and fluorine element in the first raw material is a:b:c:d, wherein a, b, c, d are real numbers greater than 0, and a, b, c, d satisfy: when a / c≤1.5, a / b<1.5, a / d<1, or when a / c≥1.5, c / b<1, c / d<2 / 3.
[0041] S102: The first raw material is processed to obtain a first precursor.
[0042] S103: The first precursor is dried and calcined to obtain sodium vanadium fluorophosphate.
[0043] In the related art, during the preparation process of sodium vanadium fluorophosphate (Na3V2(PO4)2F3), impurities such as sodium vanadium phosphate (Na3V2(PO4)3) are generated. The specific capacity and potential platform of Na3V2(PO4)3 are lower than those of Na3V2(PO4)2F3, which leads to a decrease in the working voltage and discharge specific capacity of the material, affecting the energy density of the battery made therefrom. The present application adjusts the molar ratio of sodium, vanadium, phosphorus, and fluorine in the raw materials so that the vanadium and fluorine elements in the raw materials are excessive, thereby compensating for the loss of vanadium and fluorine elements in the preparation process, thereby reducing the generation of Na3V2(PO4)3 impurities and improving the purity of the obtained Na3V2(PO4)2F3, thereby ensuring the performance of Na3V2(PO4)2F3. The preparation method is simple. Only by adjusting the ratio of each element in the raw material can the impurity content be significantly reduced to obtain Na3V2(PO4)2F3 with excellent performance. The preparation method is simple to operate, short in preparation process and high in preparation efficiency, which is conducive to the industrial production of Na3V2(PO4)2F3 and facilitates the use of Na3V2(PO4)2F3.
[0044] In S101, a first raw material is obtained by mixing a sodium source, a vanadium source, a phosphorus source, and a fluorine source in appropriate proportions. Taking the sodium element as an example, the sodium element in the first raw material comes from the sodium source, or may come from other raw materials, and the molar amount of the sodium element in the first raw material is the sum of the molar amounts of all sodium elements in the first raw material. Similarly, the molar amount of the vanadium element in the first raw material is the sum of the molar amounts of all vanadium elements in the first raw material, the molar amount of the phosphorus element in the first raw material is the sum of the molar amounts of all phosphorus elements in the first raw material, and the molar amount of the fluorine element in the first raw material is the sum of the molar amounts of all fluorine elements in the first raw material.
[0045] In the present application, the molar ratio of sodium, vanadium, phosphorus and fluorine in the first raw material is a:b:c:d, and a, b, c and d can be selected from any real number greater than 0 as needed. When a / c<1.5, that is, the ratio of a to c is less than 3:2, the phosphorus is excessive compared with the sodium; when a / c>1.5, that is, the ratio of a to c is greater than 3:2, the sodium is excessive compared with the phosphorus; when a / c=1.5, that is, the ratio of a to c is 3:2, and the sodium and phosphorus meet the molar ratio of Na to P in Na3V2(PO4)2F3. When a / c≤1.5, a / b<1.5, a / d<1, that is, the molar ratio of sodium to vanadium is less than 1.5, and the molar ratio of sodium to fluorine is less than 1. According to the molar ratio of Na to V and the molar ratio of Na to F in Na3V2(PO4)2F3, it can be seen that the first raw material contains excessive vanadium and fluorine. When a / c≥1.5, c / b<1, c / d<2 / 3, that is, the molar ratio of phosphorus to vanadium is less than 1, and the molar ratio of phosphorus to fluorine is less than 2 / 3. According to the molar ratio of P to V and the molar ratio of P to F in Na3V2(PO4)2F3, it can be seen that the first raw material contains excessive vanadium and fluorine. Therefore, by making the vanadium and fluorine elements in the first raw material excessive, the generation of Na3V2(PO4)3 impurity phase can be avoided. It can be understood that when a / c=1.5, while satisfying the conditions of a / b<1.5 and a / d<1, the conditions of c / b<1 and c / d<2 / 3 are also satisfied.
[0046] In one embodiment of the present application, when a / c≤1.5, 1.36<a / b<1.5, 0.83<a / d<1, which can not only make up for the loss of vanadium and fluorine elements in the preparation process of Na3V2(PO4)2F3 and reduce the impurity content of Na3V2(PO4)3, but also supplement the appropriate amount of vanadium and fluorine elements to ensure the cycle performance and rate performance of the prepared Na3V2(PO4)2F3. Specifically, when a / c≤1.5, a / b may be, but is not limited to, greater than or equal to 1.363, greater than or equal to 1.37, greater than or equal to 1.38, greater than or equal to 1.39, greater than or equal to 1.42, greater than or equal to 1.43, greater than or equal to 1.45, etc., a / b may be, but is not limited to, less than or equal to 1.43, less than or equal to 1.44, less than or equal to 1.45, less than or equal to 1.46, less than or equal to 1.47, less than or equal to 1.48, less than or equal to 1.49, etc.; a / d may be, but is not limited to, greater than or equal to 0.833, greater than or equal to 0.84, greater than or equal to 1.46, less than or equal to 1.47, less than or equal to 1.48, less than or equal to 1.49, etc. a / d may be, but is not limited to, less than or equal to 0.91, less than or equal to 0.92, less than or equal to 0.9375, less than or equal to 0.94, less than or equal to 0.95, less than or equal to 0.96, less than or equal to 0.97, less than or equal to 0.98, less than or equal to 0.99, etc.; a / d may be, but is not limited to, less than or equal to 0.91, less than or equal to 0.92, less than or equal to 0.9375, less than or equal to 0.94, less than or equal to 0.95, less than or equal to 0.96, less than or equal to 0.97, less than or equal to 0.98, less than or equal to 0.99, etc.
[0047] In one embodiment of the present application, when a / c≤1.5, b is 2a / 3+e, d is a+3e, and e>0. That is, when the molar ratio of sodium to vanadium is 3:2, the molar ratio of Na to V in Na3V2(PO4)2F3 is satisfied, and in the present application, b is 2a / 3+e, that is, the vanadium content is increased by the amount of e, so that the vanadium element is excessive relative to the sodium element, compensating for the loss of vanadium in the preparation process of Na3V2(PO4)2F3; when the molar ratio of sodium to fluorine is 1:1, the molar ratio of Na to F in Na3V2(PO4)2F3 is satisfied, and in the present application, d is a+3 e, that is, the fluorine content is increased by 3e, so that the fluorine element is excessive relative to the sodium element, thereby compensating for the loss of fluorine in the preparation process of Na3V2(PO4)2F3; at the same time, the amounts of vanadium and fluorine added relative to the sodium element are e and 3e respectively, that is, the amount of fluorine added relative to the sodium element is 3 times the amount of vanadium added relative to the sodium element, thereby further avoiding the generation of Na3V2(PO4)3 impurities and improving the purity of the prepared Na3V2(PO4)2F3.
[0048] In one embodiment of the present application, when a / c≤1.5, 2.5≤a≤3.5, 0<e≤0.2, this is conducive to reducing the generation of Na3V2(PO4)3 impurity phase, and can further improve the performance of Na3V2(PO4)2F3. Specifically, e can be but not limited to greater than or equal to 0.02, greater than or equal to 0.05, greater than or equal to 0.06, greater than or equal to 0.09, greater than or equal to 0.1, greater than or equal to 0.11, greater than or equal to 0.15, etc., and e can be but not limited to less than or equal to 0.09, less than or equal to 0.1, less than or equal to 0.12, less than or equal to 0.15, less than or equal to 0.16, less than or equal to 0.18, less than or equal to 0.19, less than or equal to 0.2, etc. In one embodiment of the present application, when a / c≤1.5, 2.5≤a≤3.5, and 0.1≤e≤0.2, the impurity content in Na3V2(PO4)2F3 can be further reduced, and the performance of the obtained Na3V2(PO4)2F3 can be further improved.
[0049] In one embodiment of the present application, when a / c≤1.5, 12.5≤a / e≤35, which is beneficial to reduce the generation of Na3V2(PO4)3 impurity phase and can further improve the performance of Na3V2(PO4)2F3. Specifically, a / e can be but not limited to greater than or equal to 12.5, greater than or equal to 15, greater than or equal to 18, greater than or equal to 20, greater than or equal to 25, greater than or equal to 30, etc., and a / e can be but not limited to less than or equal to 20, less than or equal to 23, less than or equal to 25, less than or equal to 28, less than or equal to 30, less than or equal to 35, etc.
[0050] In one embodiment of the present application, when a / c≥1.5, 0.89<c / b<1, 0.55<c / d<2 / 3, which can not only make up for the loss of vanadium and fluorine elements in the preparation process of Na3V2(PO4)2F3 and reduce the impurity content of Na3V2(PO4)3, but also supplement the appropriate amount of vanadium and fluorine elements to ensure the cycle performance and rate performance of the prepared Na3V2(PO4)2F3. Specifically, when a / c≥1.5, c / b may be, but is not limited to, greater than or equal to 0.899, greater than or equal to 0.9, greater than or equal to 0.91, greater than or equal to 0.92, greater than or equal to 0.93, greater than or equal to 0.94, greater than or equal to 0.95, greater than or equal to 0.96, greater than or equal to 0.97, etc., and c / b may be, but is not limited to, less than or equal to 0.95, less than or equal to 0.96, less than or equal to 0.97, less than or equal to 0.98, less than or equal to 0.99, etc.; c / d It can be, but is not limited to, greater than or equal to 0.555, greater than or equal to 0.56, greater than or equal to 0.57, greater than or equal to 0.58, greater than or equal to 0.59, greater than or equal to 0.6, greater than or equal to 0.61, greater than or equal to 0.62, greater than or equal to 0.63, etc., and c / d can be, but is not limited to, less than or equal to 0.6, less than or equal to 0.61, less than or equal to 0.62, less than or equal to 0.63, less than or equal to 0.64, less than or equal to 0.65, less than or equal to 0.66, etc.
[0051] In one embodiment of the present application, when a / c≥1.5, b is c+f, d is 1.5c+3f, and f>0. That is, when the molar ratio of phosphorus to vanadium is 1:1, the molar ratio of P to V in Na3V2(PO4)2F3 is satisfied, and in the present application, b is c+f, that is, the vanadium content is increased by the amount of f, so that the vanadium element is excessive relative to the phosphorus element, compensating for the loss of vanadium in the preparation process of Na3V2(PO4)2F3; when the molar ratio of phosphorus to fluorine is 2:3, the molar ratio of P to F in Na3V2(PO4)2F3 is satisfied, and in the present application, d is 1.5c+3f That is, the fluorine content is increased by 3e, so that the fluorine element is excessive relative to the sodium element, making up for the loss of fluorine in the preparation process of Na3V2(PO4)2F3; at the same time, the amount of vanadium and fluorine added relative to the phosphorus element is f and 3f respectively, that is, the amount of fluorine added relative to the phosphorus element is 3 times the amount of vanadium added relative to the phosphorus element, thereby further avoiding the generation of Na3V2(PO4)3 impurities and improving the purity of the obtained Na3V2(PO4)2F3.
[0052] In one embodiment of the present application, when a / c≥1.5, 1.6<c<2.4, 0<f≤0.2, which is beneficial to reduce the generation of Na3V2(PO4)3 impurity phase and can further improve the performance of Na3V2(PO4)2F3. Specifically, f can be but not limited to greater than or equal to 0.02, greater than or equal to 0.05, greater than or equal to 0.06, greater than or equal to 0.09, greater than or equal to 0.1, greater than or equal to 0.11, greater than or equal to 0.15, etc., and f can be but not limited to less than or equal to 0.09, less than or equal to 0.1, less than or equal to 0.12, less than or equal to 0.15, less than or equal to 0.16, less than or equal to 0.18, less than or equal to 0.19, less than or equal to 0.2, etc. In one embodiment of the present application, when a / c≥1.5, 1.6<c<2.4, 0.1≤f≤0.2, the impurity content in Na3V2(PO4)2F3 can be further reduced, and the performance of the obtained Na3V2(PO4)2F3 can be further improved.
[0053] In one embodiment of the present application, when a / c≥1.5, 8.3<c / f<23.4, which is beneficial to reduce the generation of Na3V2(PO4)3 impurity phase and can further improve the performance of Na3V2(PO4)2F3. Specifically, c / f can be but not limited to greater than or equal to 9, greater than or equal to 10, greater than or equal to 12, greater than or equal to 15, greater than or equal to 18, greater than or equal to 20, etc., and c / f can be but not limited to less than or equal to 15, less than or equal to 18, less than or equal to 20, less than or equal to 21, less than or equal to 22, less than or equal to 23, etc.
[0054] It is understandable that the sodium source, vanadium source, phosphorus source, and fluorine source refer to materials that can provide sodium, vanadium, phosphorus, and fluorine elements, respectively. In one embodiment of the present application, the sodium source includes at least one of sodium fluoride, sodium carbonate, sodium oxalate, sodium sulfate, and sodium metavanadate. In one embodiment of the present application, the vanadium source includes at least one of ammonium metavanadate, vanadium pentoxide, vanadium acetylacetonate, sodium metavanadate, vanadium trifluoride, vanadium tetrafluoride, and trifluoro vanadium oxide. In one embodiment of the present application, the phosphorus source (such as a phosphate source) includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate. In one embodiment of the present application, the fluorine source includes at least one of sodium fluoride, ammonium fluoride, hydrofluoric acid, vanadium trifluoride, vanadium tetrafluoride, and trifluoro vanadium oxide. In the present application, the purity of the sodium source, vanadium source, phosphorus source, and fluorine source may be greater than or equal to 95%, greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, greater than or equal to 99%, greater than or equal to 99.8%, greater than or equal to 99.9%, greater than or equal to 99.99%, etc.
[0055] In one embodiment of the present application, when the valence of the vanadium element in the vanadium source is +5 or +4, the first raw material also includes a reducing agent. In one embodiment of the present application, the reducing agent includes at least one of citric acid, oxalic acid, glucose, fructose, ascorbic acid, carbon nanotubes, conductive carbon black (such as Super P, etc.) and graphene oxide. By adding a reducing agent, vanadium with a valence of +5 or +4 can be reduced to vanadium with a valence of +3, thereby ensuring the preparation of Na3V2(PO4)2F3. In one embodiment of the present application, when a / c≤1.5, the molar ratio of the sodium element and the reducing agent in the first raw material is greater than or equal to 3, and when a / c≥1.5, the molar ratio of the phosphorus element and the reducing agent in the first raw material is greater than or equal to 2, thereby ensuring the reduction of vanadium, while also ensuring the consumption of the reducing agent, and no carbon coating will be produced.
[0056] In S102, the first raw material is processed to obtain a first precursor. In one embodiment of the present application, the first raw material is processed to obtain a first precursor, including: the first raw material is processed by at least one of a solid phase method, a hydrothermal method, a sol-gel method and a spray drying method to obtain the first precursor.
[0057] In one embodiment of the present application, the first raw material is treated by a solid phase method to obtain a first precursor, including: adding the first raw material to a solvent and then ball milling to obtain the first precursor. Specifically, the ball milling medium can be but is not limited to zirconium beads, and the solvent can be but is not limited to at least one of water, acetone, anhydrous ethanol, ethylene glycol, etc.
[0058] In one embodiment of the present application, the first raw material is subjected to a hydrothermal treatment to obtain a first precursor, comprising: adding water to the first raw material and placing it in a hydrothermal reactor, reacting at 150°C-220°C (such as 150°C, 160°C, 180°C, 200°C, 210°C, 215°C, etc.) for 10h-15h (such as 10h, 11h, 12h, 13h, 14h, 15h, etc.) and then centrifuging to obtain the first precursor. Specifically, the centrifugation can be, but is not limited to, centrifuging at 8000rmp-15000rmp (such as 10000rmp, 12000rmp, 13000rmp, 14000rmp, etc.) for 2min-10min (such as 3min, 5min, 8min, 9min, etc.).
[0059] In one embodiment of the present application, the first raw material is treated by a sol-gel method to obtain a first precursor, including: adding the first raw material to a solvent to react to obtain a gel-like first precursor. Specifically, the first raw material is directly added to the solvent after mixing, or the weighed raw materials can be added to the solvent in sequence. The vanadium source and the reducing agent can be added to the solvent at the same time, or the reducing agent can be added after the vanadium source is added to the solvent.
[0060] In one embodiment of the present application, the first raw material is treated by spray drying to obtain a first precursor, including: adding the first raw material to a solvent to form a first solution, and spray drying the first solution to obtain a first precursor. Specifically, the solvent may be, but is not limited to, at least one of water, acetone, anhydrous ethanol, ethylene glycol, etc.; the vanadium source and the reducing agent are added to the solvent at the same time, or the vanadium source is added to the solvent and then the reducing agent is added. In one embodiment of the present application, the feed temperature in spray drying can be 180°C-220°C (such as 190°C, 200°C, 210°C, 215°C, etc.), the feed rate can be 180mL / h-220mL / h (such as 185mL / h, 190mL / h, 200mL / h, 210mL / h, etc.), and the fan frequency can be 70HZ-90HZ (such as 75HZ, 80HZ, 85HZ, 90HZ, etc.). The first precursor obtained by spray drying does not need to undergo subsequent drying treatment, thus saving preparation process and improving preparation efficiency.
[0061] In S103, the first precursor is dried and calcined to obtain sodium vanadium fluorophosphate. The drying can remove the solvent, water, etc. in the first precursor, increase the solid content of the first precursor, and generate +3 valence vanadium under the action of the reducing agent during the calcination process to produce Na3V2(PO4)2F3.
[0062] In one embodiment of the present application, drying includes treating at 100°C-120°C for 1h-3h. Specifically, the drying temperature may be, but not limited to, 100°C, 105°C, 108°C, 110°C, 115°C, 117°C or 120°C, and the drying time may be, but not limited to, 1h, 1.5h, 2h, 2.5h or 3h, etc. In the present application, drying may be performed in a vacuum environment.
[0063] In one embodiment of the present application, calcination includes treating at 300°C-400°C (such as 320°C, 350°C, 360°C, 380°C, etc.) for 1h-5h (such as 2h, 3h, 4h, 4.5h, 5h, etc.), and then treating at 600°C-800°C (such as 650°C, 700°C, 750°C, 790°C, etc.) for 10min-10h (such as 20min, 30min, 50min, 1h, 3h, 4h, 6h, 7h, 8h, 9h, 10h, etc.). In order to avoid the generation of impurities caused by fluorine volatilization, the relevant technology will adopt a lower calcination temperature and a shorter calcination time. In the present application, the first raw material has an excess of fluorine and vanadium elements, so that the impurities generated by fluorine volatilization can be reduced, so there is no need to reduce the calcination temperature and shorten the calcination time, thereby ensuring that the calcination is fully carried out to obtain Na3V2(PO4)2F3 with excellent performance. In one embodiment of the present application, calcination is carried out under an inert gas to ensure the performance of the obtained Na3V2(PO4)2F3; specifically, the inert gas can be, but is not limited to, argon. In the present application, calcination can be carried out in a tubular furnace (such as an ordinary tubular furnace, a microwave tubular furnace, etc.) or a sintering furnace. In one embodiment of the present application, calcination is carried out in a microwave tubular furnace, including treatment at 300°C-400°C for 1h-5h, and then treatment at 600°C-800°C for 10min-60min. Due to the fast heating rate of the microwave tubular furnace (about 20°C / min-50°C / min), it can be heated to the target temperature in a short time, achieving rapid calcination, and avoiding the loss of fluorine and vanadium. In one embodiment of the present application, a heating rate of 3°C / min-8°C / min (such as 4°C / min, 5°C / min, 6°C / min, 7°C / min, etc.) is used in calcination to heat to 300°C-400°C.
[0064] See also Figure 2 , is a flow chart of a method for preparing carbon-coated sodium vanadium fluorophosphate provided in one embodiment of the present application, comprising:
[0065] S201: A sodium source, a vanadium source, a phosphorus source, a fluorine source and a carbon source are mixed to form a second raw material, wherein the molar ratio of the sodium element, the vanadium element, the phosphorus element and the fluorine element in the second raw material is a':b':c':d', wherein a', b', c', d' are real numbers greater than 0, and a', b', c', d' satisfy: when a' / c'≤1.5, a' / b'<1.5, a' / d'<1, or when a' / c'≥1.5, c' / b'<1, c' / d'<2 / 3.
[0066] S202: The second raw material is processed to obtain a second precursor.
[0067] S203: The second precursor is dried and calcined to obtain carbon-coated sodium vanadium fluorophosphate.
[0068] In the preparation method of carbon-coated sodium vanadium fluorophosphate (Na3V2(PO4)2F3@C) provided in the present application, the molar ratio of sodium, vanadium, phosphorus and fluorine is controlled to reduce the content of impurities in sodium vanadium fluorophosphate, and carbon coating can also improve the conductivity of sodium vanadium fluorophosphate, thereby obtaining a material with high purity and excellent performance; and the preparation method is simple to operate, has a short preparation process and high preparation efficiency, which is conducive to the industrial production of carbon-coated sodium vanadium fluorophosphate and the use of carbon-coated sodium vanadium fluorophosphate. It can be understood that the difference between the carbon-coated sodium vanadium fluorophosphate provided in the present application and the preparation method of sodium vanadium fluorophosphate in any of the above embodiments is that more carbon source is added to the raw material, so that a carbon coating layer can be formed on the surface of sodium vanadium fluorophosphate after drying and sintering.
[0069] In S201, a second raw material is obtained by mixing a sodium source, a vanadium source, a phosphorus source, a fluorine source and a carbon source in appropriate proportions. Taking the sodium element as an example, the sodium element in the second raw material comes from the sodium source, or it can come from other raw materials. The molar amount of the sodium element in the second raw material is the sum of the molar amounts of all sodium elements in the second raw material. Similarly, the molar amount of the vanadium element in the second raw material is the sum of the molar amounts of all vanadium elements in the second raw material, the molar amount of the phosphorus element in the second raw material is the sum of the molar amounts of all phosphorus elements in the second raw material, and the molar amount of the fluorine element in the second raw material is the sum of the molar amounts of all fluorine elements in the second raw material.
[0070] In the present application, the molar ratio of sodium, vanadium, phosphorus and fluorine in the second raw material is a':b':c':d', and a', b', c', d' can be selected from any real number greater than 0 as needed. When a' / c'≤1.5, that is, the ratio of a' to c' is less than 3:2, and the phosphorus element is excessive compared with the sodium element; when a' / c'>1.5, that is, the ratio of a' to c' is greater than 3:2, and the sodium element is excessive compared with the phosphorus element; when a' / c'=1.5, that is, the ratio of a' to c' is 3:2, and the sodium element and the phosphorus element meet the molar ratio of Na to P in Na3V2(PO4)2F3. When a' / c'≤1.5, a' / b'<1.5, a' / d'<1, that is, the molar ratio of sodium to vanadium is less than 1.5, and the molar ratio of sodium to fluorine is less than 1. According to the molar ratio of Na to V and the molar ratio of Na to F in Na3V2(PO4)2F3, it can be seen that the second raw material contains excessive vanadium and fluorine. When a' / c'≥1.5, c' / b'<1, c' / d'<2 / 3, that is, the molar ratio of phosphorus to vanadium is less than 1, and the molar ratio of phosphorus to fluorine is less than 2 / 3. According to the molar ratio of P to V and the molar ratio of P to F in Na3V2(PO4)2F3, it can be seen that the second raw material contains excessive vanadium and fluorine. Therefore, by making the vanadium and fluorine elements in the second raw material excessive, the generation of Na3V2(PO4)3 impurity phase can be avoided. It can be understood that when a' / c'=1.5, the conditions of a' / b'<1.5 and a' / d'<1 are satisfied, and the conditions of c' / b'<1 and c' / d'<2 / 3 are also satisfied.
[0071] In one embodiment of the present application, when a' / c'≤1.5, 1.36<a' / b'<1.5, 0.83<a' / d'<1, which can not only make up for the loss of vanadium and fluorine elements in the preparation process of Na3V2(PO4)2F3@C and reduce the content of Na3V2(PO4)3 impurities, but also supplement the appropriate amount of vanadium and fluorine elements to ensure the cycle performance and rate performance of the prepared Na3V2(PO4)2F3@C. Specifically, when a' / c'≤1.5, a' / b' may be, but is not limited to, greater than or equal to 1.363, greater than or equal to 1.37, greater than or equal to 1.38, greater than or equal to 1.39, greater than or equal to 1.42, greater than or equal to 1.43, greater than or equal to 1.45, etc., a' / b' may be, but is not limited to, less than or equal to 1.43, less than or equal to 1.44, less than or equal to 1.45, less than or equal to 1.46, less than or equal to 1.47, less than or equal to 1.48, less than or equal to 1.49, etc.; a' / d' may be, but is not limited to, greater than or equal to 0.833, greater than or equal to 0.84, greater than or equal to 1.46, less than or equal to 1.47, less than or equal to 1.48, less than or equal to 1.49, etc. The ratio of a' to d' may be, but is not limited to, less than or equal to 0.91, less than or equal to 0.92, less than or equal to 0.9375, less than or equal to 0.94, less than or equal to 0.95, less than or equal to 0.96, less than or equal to 0.97, less than or equal to 0.98, less than or equal to 0.99, etc.; the ratio of a' to d' may be, but is not limited to, less than or equal to 0.91, less than or equal to 0.92, less than or equal to 0.9375, less than or equal to 0.94, less than or equal to 0.95, less than or equal to 0.96, less than or equal to 0.97, less than or equal to 0.98, less than or equal to 0.99, etc.
[0072] In one embodiment of the present application, when a' / c'≤1.5, b' is 2a' / 3+e', d' is a'+3e', and e'>0. That is, when the molar ratio of sodium to vanadium is 3:2, the molar ratio of Na to V in Na3V2(PO4)2F3 is satisfied, and in the present application, b' is 2a' / 3+e', that is, the vanadium content is increased by the amount of e', so that the vanadium element is excessive relative to the sodium element, compensating for the loss of vanadium in the preparation process of Na3V2(PO4)2F3@C; when the molar ratio of sodium to fluorine is 1:1, the molar ratio of Na to F in Na3V2(PO4)2F3 is satisfied, and in the present application, d' is a'+3 e', that is, the fluorine content is increased by 3e', so that the fluorine element is excessive relative to the sodium element, thereby compensating for the loss of fluorine in the preparation process of Na3V2(PO4)2F3@C; at the same time, the amount of vanadium and fluorine added relative to the sodium element is e' and 3e' respectively, that is, the amount of fluorine added relative to the sodium element is 3 times the amount of vanadium added relative to the sodium element, thereby further avoiding the generation of Na3V2(PO4)3 impurities and improving the purity of the prepared Na3V2(PO4)2F3@C.
[0073] In one embodiment of the present application, when a' / c'≤1.5, 2.5≤a'≤3.5, 0<e'≤0.2, this is conducive to reducing the generation of Na3V2(PO4)3 impurity phase, and can further improve the performance of Na3V2(PO4)2F3@C. Specifically, e' can be but not limited to greater than or equal to 0.02, greater than or equal to 0.05, greater than or equal to 0.06, greater than or equal to 0.09, greater than or equal to 0.1, greater than or equal to 0.11, greater than or equal to 0.15, etc., and e' can be but not limited to less than or equal to 0.09, less than or equal to 0.1, less than or equal to 0.12, less than or equal to 0.15, less than or equal to 0.16, less than or equal to 0.18, less than or equal to 0.19, less than or equal to 0.2, etc. In one embodiment of the present application, when a' / c'≤1.5, 2.5≤a'≤3.5, 0.1≤e'≤0.2, the impurity content in Na3V2(PO4)2F3@C can be further reduced, and the performance of the obtained Na3V2(PO4)2F3@C can be further improved.
[0074] In one embodiment of the present application, when a' / c'≤1.5, 12.5≤a' / e'≤35, which is beneficial to reduce the generation of Na3V2(PO4)3 impurity phase and can further improve the performance of Na3V2(PO4)2F3@C. Specifically, a' / e' can be but not limited to greater than or equal to 12.5, greater than or equal to 15, greater than or equal to 18, greater than or equal to 20, greater than or equal to 25, greater than or equal to 30, etc., and a' / e' can be but not limited to less than or equal to 20, less than or equal to 23, less than or equal to 25, less than or equal to 28, less than or equal to 30, less than or equal to 35, etc.
[0075] In one embodiment of the present application, when a' / c'≥1.5, 0.89<c' / b'<1, 0.55<c' / d'<2 / 3, which can not only make up for the loss of vanadium and fluorine elements in the preparation process of Na3V2(PO4)2F3@C and reduce the content of Na3V2(PO4)3 impurities, but also supplement the appropriate amount of vanadium and fluorine elements to ensure the cycle performance and rate performance of the prepared Na3V2(PO4)2F3@C. Specifically, when a' / c'≥1.5, c' / b' may be, but is not limited to, greater than or equal to 0.899, greater than or equal to 0.9, greater than or equal to 0.91, greater than or equal to 0.92, greater than or equal to 0.93, greater than or equal to 0.94, greater than or equal to 0.95, greater than or equal to 0.96, greater than or equal to 0.97, etc., and c' / b' may be, but is not limited to, less than or equal to 0.95, less than or equal to 0.96, less than or equal to 0.97, less than or equal to 0.98, less than or equal to 0.99, etc.; c' / d' can be, but is not limited to, greater than or equal to 0.555, greater than or equal to 0.56, greater than or equal to 0.57, greater than or equal to 0.58, greater than or equal to 0.59, greater than or equal to 0.6, greater than or equal to 0.61, greater than or equal to 0.62, greater than or equal to 0.63, etc., and c' / d' can be, but is not limited to, less than or equal to 0.6, less than or equal to 0.61, less than or equal to 0.62, less than or equal to 0.63, less than or equal to 0.64, less than or equal to 0.65, less than or equal to 0.66, etc.
[0076] In one embodiment of the present application, when a' / c'≥1.5, b' is c'+f', d' is 1.5c'+3f', and f'>0. That is, when the molar ratio of phosphorus to vanadium is 1:1, the molar ratio of P to V in Na3V2(PO4)2F3 is satisfied, and in the present application, b' is c'+f', that is, the vanadium content is increased by the amount of f', so that the vanadium element is excessive relative to the phosphorus element, compensating for the loss of vanadium in the preparation process of Na3V2(PO4)2F3@C; when the molar ratio of phosphorus to fluorine is 2:3, the molar ratio of P to F in Na3V2(PO4)2F3 is satisfied, and in the present application, d' is 1.5c'+3f ', that is, the fluorine content is increased by 3e', so that the fluorine element is excessive relative to the sodium element, thereby compensating for the loss of fluorine in the preparation process of Na3V2(PO4)2F3@C; at the same time, the amount of vanadium and fluorine added relative to the phosphorus element is f' and 3f' respectively, that is, the amount of fluorine added relative to the phosphorus element is 3 times the amount of vanadium added relative to the phosphorus element, thereby further avoiding the generation of Na3V2(PO4)3 impurities and improving the purity of the prepared Na3V2(PO4)2F3@C.
[0077] In one embodiment of the present application, when a' / c'≥1.5, 1.6<c'<2.4, 0<f'≤0.2, which is beneficial to reduce the generation of Na3V2(PO4)3 impurity phase and can further improve the performance of Na3V2(PO4)2F3@C. Specifically, f' may be, but not limited to, greater than or equal to 0.02, greater than or equal to 0.05, greater than or equal to 0.06, greater than or equal to 0.09, greater than or equal to 0.1, greater than or equal to 0.11, greater than or equal to 0.15, etc., and f' may be, but not limited to, less than or equal to 0.09, less than or equal to 0.1, less than or equal to 0.12, less than or equal to 0.15, less than or equal to 0.16, less than or equal to 0.18, less than or equal to 0.19, less than or equal to 0.2, etc. In one embodiment of the present application, when a' / c'≥1.5, 1.6<c'<2.4, 0.1≤f'≤0.2, the impurity content in Na3V2(PO4)2F3@C can be further reduced, and the performance of the obtained Na3V2(PO4)2F3@C can be further improved.
[0078] In one embodiment of the present application, when a / c≥1.5, 8.3<c' / f'<23.4, which is beneficial to reduce the generation of Na3V2(PO4)3 impurity phase and can further improve the performance of Na3V2(PO4)2F3@C. Specifically, c' / f' can be but not limited to greater than or equal to 9, greater than or equal to 10, greater than or equal to 12, greater than or equal to 15, greater than or equal to 18, greater than or equal to 20, etc., and c' / f' can be but not limited to less than or equal to 15, less than or equal to 18, less than or equal to 20, less than or equal to 21, less than or equal to 22, less than or equal to 23, etc.
[0079] It is understandable that the sodium source, vanadium source, phosphorus source, fluorine source, and carbon source refer to materials that can provide sodium, vanadium, phosphorus, fluorine, and carbon elements, respectively. In one embodiment of the present application, the sodium source includes at least one of sodium fluoride, sodium carbonate, sodium oxalate, sodium sulfate, and sodium metavanadate. In one embodiment of the present application, the vanadium source includes at least one of ammonium metavanadate, vanadium pentoxide, vanadium acetylacetonate, sodium metavanadate, vanadium trifluoride, vanadium tetrafluoride, and trifluoro vanadium oxide. In one embodiment of the present application, the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate. In one embodiment of the present application, the fluorine source includes at least one of sodium fluoride, ammonium fluoride, hydrofluoric acid, vanadium trifluoride, vanadium tetrafluoride, and trifluoro vanadium oxide. In one embodiment of the present application, the carbon source includes at least one of citric acid, oxalic acid, glucose, fructose, sucrose, and ascorbic acid. In the present application, the purity of the sodium source, vanadium source, phosphorus source, fluorine source, and carbon source may be greater than or equal to 95%, greater than or equal to 96%, greater than or equal to 97%, greater than or equal to 98%, greater than or equal to 99%, greater than or equal to 99.8%, greater than or equal to 99.9%, greater than or equal to 99.99%, etc.
[0080] In one embodiment of the present application, when a' / c'≤1.5, the molar ratio of sodium element to carbon element in the second raw material is 3:(1-4), and when a' / c'≥1.5, the molar ratio of phosphorus element to carbon element in the second raw material is 2:(1-4), thereby ensuring the formation of a carbon coating layer and improving the electrical conductivity of Na3V2(PO4)2F3@C.
[0081] In one embodiment of the present application, when the valence of the vanadium element in the vanadium source is +5 or +4, the second raw material also includes a reducing agent. In one embodiment of the present application, the reducing agent includes at least one of citric acid, oxalic acid, glucose, fructose, ascorbic acid, carbon nanotubes, conductive carbon black (such as Super P, etc.) and graphene oxide. By adding a reducing agent, the vanadium with a valence of +5 or +4 can be reduced to vanadium with a valence of +3, thereby ensuring the preparation of Na3V2(PO4)2F3@C. In one embodiment of the present application, when a' / c'≤1.5, the molar ratio of the sodium element and the reducing agent in the second raw material is greater than or equal to 3, and when a' / c'≥1.5, the molar ratio of the phosphorus element and the reducing agent in the second raw material is greater than or equal to 2, thereby ensuring the reduction of vanadium, and also ensuring the consumption of the reducing agent, and no carbon coating will be produced. In the present application, when the carbon source has reducing properties, it can also be used as a reducing agent at the same time, thereby avoiding the addition of additional reducing agents, reducing the amount of raw materials, and reducing the preparation cost.
[0082] In S202, the second raw material is processed to obtain a second precursor. In one embodiment of the present application, the second raw material is processed to obtain a second precursor, including: the second raw material is processed by at least one of a solid phase method, a hydrothermal method, a sol-gel method, and a spray drying method to obtain the second precursor. The specific processes of the solid phase method, the hydrothermal method, the sol-gel method, and the spray drying method are as described above and will not be repeated here.
[0083] In S203, the second precursor is dried and calcined to obtain sodium vanadium fluorophosphate. The drying can remove the solvent, water, etc. in the second precursor, increase the solid content of the second precursor, and generate +3 valence vanadium under the action of the reducing agent during the calcination process to produce Na3V2(PO4)2F3@C.
[0084] In one embodiment of the present application, drying includes treating at 100°C-120°C for 1h-3h. Specifically, the drying temperature may be, but not limited to, 100°C, 105°C, 108°C, 110°C, 115°C, 117°C or 120°C, and the drying time may be, but not limited to, 1h, 1.5h, 2h, 2.5h or 3h, etc. In the present application, drying may be performed in a vacuum environment.
[0085] In one embodiment of the present application, calcination includes treating at 300°C-400°C (such as 320°C, 350°C, 360°C, 380°C, etc.) for 1h-5h (such as 2h, 3h, 4h, 4.5h, 5h, etc.), and then treating at 600°C-800°C (such as 650°C, 700°C, 750°C, 790°C, etc.) for 10min-10h (such as 20min, 30min, 50min, 1h, 3h, 4h, 6h, 7h, 8h, 9h, 10h, etc.). In order to avoid the generation of impurities caused by fluorine volatilization, the relevant technology will adopt a lower calcination temperature and a shorter calcination time. In the present application, the second raw material has an excess of fluorine and vanadium elements, so that the impurities generated by fluorine volatilization can be reduced, so there is no need to reduce the calcination temperature and shorten the calcination time, thereby ensuring that the calcination is fully carried out to obtain Na3V2(PO4)2F3@C with excellent performance. In one embodiment of the present application, calcination is carried out under an inert gas to ensure the performance of the obtained Na3V2(PO4)2F3@C; specifically, the inert gas can be, but is not limited to, argon. In the present application, calcination can be carried out in a tubular furnace (such as an ordinary tubular furnace, a microwave tubular furnace, etc.) or a sintering furnace. In one embodiment of the present application, calcination is carried out in a microwave tubular furnace, including treatment at 300°C-400°C for 1h-5h, and then treatment at 600°C-800°C for 10min-60min. Due to the fast heating rate of the microwave tubular furnace (about 20°C / min-50°C / min), it can be heated to the target temperature in a short time, achieving rapid calcination, and avoiding the loss of fluorine and vanadium. In one embodiment of the present application, a heating rate of 3°C / min-8°C / min (such as 4°C / min, 5°C / min, 6°C / min, 7°C / min, etc.) is used in calcination to heat to 300°C-400°C.
[0086] In one embodiment of the present application, the particle size D50 of the carbon-coated sodium vanadium fluorophosphate is 100nm-3000nm. Specifically, the particle size D50 of the carbon-coated sodium vanadium fluorophosphate can be, but is not limited to, 400nm, 500nm, 750nm, 1000nm, 1200nm, 1500nm, 1700nm, 2000nm, 2300nm, 2300nm or 2800nm, etc. The particle size D50 of the carbon-coated sodium vanadium fluorophosphate prepared in the present application is adapted so that it has a suitable tap density, which is conducive to the use of the carbon-coated sodium vanadium fluorophosphate.
[0087] In one embodiment of the present application, the mass content of carbon in the carbon-coated sodium vanadium fluorophosphate is 5%-15%, which helps to improve its electronic conductivity. Specifically, the mass content of carbon in the carbon-coated sodium vanadium fluorophosphate can be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc.
[0088] The carbon-coated sodium vanadium fluorophosphate prepared in the present application includes sodium vanadium fluorophosphate and a carbon coating layer coating the sodium vanadium fluorophosphate. The electronic conductivity of the sodium vanadium fluorophosphate can be increased by providing the carbon coating layer, thereby improving the electrical properties of the material.
[0089] The present application also provides a battery pole piece, comprising at least one of the sodium vanadium fluorophosphate prepared in any of the above embodiments and the carbon-coated sodium vanadium fluorophosphate prepared in any of the above embodiments. The specific capacity and energy density of the battery pole piece provided in the present application are conducive to the use of the battery pole piece. The battery pole piece can be a positive electrode or a negative electrode, and the sodium vanadium fluorophosphate and the carbon-coated sodium vanadium fluorophosphate can be used as active materials in the electrode pole piece.
[0090] The following description takes the electrode plate as the positive electrode. Figure 3 , is a schematic cross-sectional view of a positive electrode provided in one embodiment of the present application, wherein the positive electrode 100 includes a positive electrode current collector 10 and a positive electrode active material layer 20 disposed on the surface of the positive electrode current collector 10, and the positive electrode active material layer 20 includes sodium vanadium fluorophosphate and / or carbon-coated sodium vanadium fluorophosphate in any of the above embodiments. The material of the positive electrode current collector may be, but is not limited to, aluminum.
[0091] It can be understood that sodium vanadium fluorophosphate and / or carbon-coated sodium vanadium fluorophosphate are positive electrode active materials. In one embodiment of the present application, the mass content of the positive electrode active material in the positive electrode active material layer is greater than or equal to 85%, thereby ensuring the electrochemical performance of the positive electrode. In other words, the total mass content of sodium vanadium fluorophosphate and carbon-coated sodium vanadium fluorophosphate in the positive electrode active material layer is greater than or equal to 85%. Specifically, the mass content of the positive electrode active material in the positive electrode active material layer can be, but is not limited to, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, etc.
[0092] In one embodiment of the present application, the positive electrode active material layer may further include a positive electrode conductive agent. Specifically, the positive electrode conductive agent includes at least one of conductive carbon black, acetylene black, carbon nanowires, graphite and graphene. In one embodiment of the present application, the mass content of the positive electrode conductive agent in the positive electrode active material layer may be 0.1%-10%. Specifically, the mass content of the positive electrode conductive agent in the positive electrode active material layer may be, but is not limited to, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.
[0093] In one embodiment of the present application, the positive electrode active material layer may also include a positive electrode binder. Specifically, the positive electrode binder may include but is not limited to polythiophene, polypyrrole, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polystyrene, polyacrylamide, ethylene-propylene-diene copolymer resin, styrene-butadiene rubber, polybutadiene, fluororubber, polyvinyl pyrrolidone, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, carboxypropyl cellulose, ethyl cellulose, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene rubber. In one embodiment of the present application, the mass content of the positive electrode binder in the positive electrode active material layer may be 0.5%-5%. Specifically, the mass content of the positive electrode binder in the positive electrode active material layer may be but is not limited to 0.5%, 1%, 2%, 3%, 4% or 5%, etc.
[0094] In the present application, the positive electrode active material can be dispersed in an organic solvent to form a positive electrode active slurry, and the positive electrode active slurry can be coated on the surface of the positive electrode current collector, and the positive electrode can be obtained after drying. Specifically, at least one of a positive electrode conductive agent and a positive electrode binder can be added to the positive electrode active slurry; the organic solvent can include but is not limited to at least one of ethanol, toluene, xylene, anisole, acetonitrile, heptane, decane, ethyl acetate, ethyl propionate, butyl butyrate, N-methylpyrrolidone, acetone, etc.
[0095] The present application also provides a battery, comprising the battery pole piece in any of the above embodiments. The battery pole piece in the battery provided by the present application has high specific capacity and energy density, so that the battery has excellent electrochemical performance and is beneficial to its use.
[0096] In one embodiment of the present application, the battery pole piece is a positive electrode, and the battery includes a battery pole piece and a negative electrode. In one embodiment of the present application, the battery also includes a separator disposed between the battery pole piece and the negative electrode. In one embodiment of the present application, the battery also includes an electrolyte. Among them, at least part of the battery pole piece and at least part of the negative electrode are immersed in the electrolyte. The present application has no special restrictions on the negative electrode, separator and electrolyte, and can be but not limited to using materials that can be used as battery negative electrodes, separators and electrolytes in the art.
[0097] The present application provides an electric device, including a battery in any of the above embodiments. The electric device provided by the present application has excellent performance and strong product competitiveness. The electric device of the present application may refer to a vehicle, an electronic device, an energy storage system, etc., and the above battery may be provided in the electric device in the form of a single cell, a battery module, a battery pack, etc.
[0098] The effects of the technical solutions provided in this application are further illustrated below through specific embodiments.
[0099] Example 1
[0100] Weigh each substance according to the molar ratio of NaF (purity of 99.9%), NH4F (purity of 98%), NH4VO3 (purity of 99.9%), NH4H2PO4 (purity of 99%), and C6H8O7·H2O (purity of 99.8%) of 3:0.3:2.1:2:2.
[0101] Add NH4VO3 to 30ml of deionized water, stir evenly at 85℃, then add C6H8O7·H2O as a reducing agent and carbon source, stir to form a blue-green solution, then add NaF, NH4F and NH4H2PO4 and stir until the solvent evaporates to obtain a gel, then place the gel in a vacuum drying oven, dry at 110℃ for 1h, remove the water in the slurry and grind to obtain a precursor powder. Place the precursor powder in a porcelain boat, put it in a tube furnace, heat it to 350℃ at 5℃ / min under a flowing argon atmosphere for 4h, then calcine it at 750℃ for 8h, and grind it to obtain Na3V2(PO4)2F3@C.
[0102] Example 2
[0103] It is substantially the same as Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.15:2.05:2:2.
[0104] Example 3
[0105] It is substantially the same as Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.45:2.15:2:2.
[0106] Example 4
[0107] It is substantially the same as Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.6:2.2:2:2.
[0108] Example 5
[0109] It is substantially the same as Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 2.5:0.6:1.867:1.667:2.
[0110] Example 6
[0111] It is substantially the same as Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.3:2.1:2.2:2.
[0112] Example 7
[0113] It is substantially the same as Example 1, except that the molar ratio of Na2CO3, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3.65:3.3:2.1:2:2.
[0114] Example 8
[0115] It is substantially the same as Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.9:2.3:2:2.
[0116] Example 9
[0117] It is roughly the same as Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.3:2.1:2:1.05, and Na3V2(PO4)2F3 is obtained.
[0118] Example 10
[0119] It is roughly the same as Example 2, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.15:2.05:2:1.025, and Na3V2(PO4)2F3 is obtained.
[0120] Embodiment 11
[0121] It is roughly the same as Example 3, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.45:2.15:2:1.075, and Na3V2(PO4)2F3 is obtained.
[0122] Example 12
[0123] It is roughly the same as Example 4, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.6:2.2:2:1.1, and Na3V2(PO4)2F3 is obtained.
[0124] Embodiment 13
[0125] It is roughly the same as Example 5, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 2.5:0.6:1.867:1.667:0.9335, and Na3V2(PO4)2F3 is obtained.
[0126] Embodiment 14
[0127] It is roughly the same as Example 6, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.3:2.1:2.2:1.05, and Na3V2(PO4)2F3 is obtained.
[0128] Embodiment 15
[0129] It is roughly the same as Example 7, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 1.65:3.3:2.1:2:1.05, and Na3V2(PO4)2F3 is obtained.
[0130] Example 16
[0131] It is roughly the same as Example 8, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.9:2.3:2:1.15, and Na3V2(PO4)2F3 is obtained.
[0132] Embodiment 17
[0133] It is roughly the same as Example 9, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:0.3:2.1:2:1.05, and Na3V2(PO4)2F3 is obtained.
[0134] Embodiment 18
[0135] It is roughly the same as Example 9, except that NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O are replaced by Na2CO3, NH4F, V2O5, NaH2PO4, and C6H8O6 (ascorbic acid), respectively, with a molar ratio of 0.5:0.3:1.05:2:1.05.
[0136] Comparative Example 1
[0137] Weigh each substance according to the molar ratio of NaF, NH4VO3, NH4H2PO4, and C6H8O7·H2O of 3:2:2:2.
[0138] Add NH4VO3 to 30ml of deionized water, stir evenly at 85℃, then add C6H8O7·H2O as a reducing agent and carbon source, stir to form a blue-green solution, then add NaF and NH4H2PO4 and stir until the solvent evaporates to obtain a gel, then place the gel in a vacuum drying oven, dry at 110℃ for 1h, remove the water in the slurry and grind to obtain a precursor powder. Place the precursor powder in a porcelain boat, put it in a tube furnace, heat it to 350℃ at 5℃ / min under a flowing argon atmosphere, keep it warm for 4h, then calcine it at 750℃ for 8h, and grind it to obtain Na3V2(PO4)2F3@C.
[0139] Comparative Example 2
[0140] It is roughly the same as Comparative Example 1, except that the molar ratio of NaF, NH4F, NH4VO3, NH4H2PO4, and C6H8O7·H2O is 3:2:2:2:1, and Na3V2(PO4)2F3 is obtained.
[0141] Performance Testing
[0142] The Na3V2(PO4)2F3@C or Na3V2(PO4)2F3 prepared in the embodiment and the comparative example were subjected to X-ray diffraction (XRD) test (test conditions: Cu target, scanning range 10°-80°, scanning speed 5° / min). Compared with the comparative example, the product prepared in the embodiment has fewer characteristic peaks of Na3V2(PO4)3 and weaker peak intensity. Some XRD patterns are shown in Fig. Figure 4 As shown, it can be seen that the diffraction peaks of Na3V2(PO4)2F3 in Na3V2(PO4)2F3@C prepared in Examples 1-4 are consistent with the diffraction peaks in the Na3V2(PO4)2F3 standard card (PDF#00-066-0372), corresponding to the P42 / mnm space group with a tetragonal symmetric index. Compared with the diffraction peaks in the Na3V2(PO4)3 standard card (PDF#00-062-0345), the characteristic peaks of Na3V2(PO4)3 in Example 1, Example 3 and Example 4 are fewer and the peak intensity is weaker. The characteristic peak intensity of Na3V2(PO4)3 in Example 2 is slightly stronger than that in Example 1, Example 3 and Example 4, but weaker than the characteristic peak intensity of Na3V2(PO4)3 in Comparative Example 1. The characteristic peak of Na3V2(PO4)3 in Comparative Example 1 is obvious; therefore, the preparation method provided in the present application can reduce the generation of Na3V2(PO4)3 impurities in Na3V2(PO4)2F3.
[0143] Example 1-4: The Na3V2(PO4)2F3@C prepared in Example 1 was subjected to thermogravimetric analysis (TG) test. The TG curve is shown in FIG. Figure 5As shown; wherein, the TG test includes taking 8 mg of Na3V2(PO4)2F3@C, testing it at a heating rate of 5°C / min under an oxygen atmosphere, and determining the carbon material content therein, and the results are shown in Table 1. It can be seen that the average content of carbon material in Na3V2(PO4)2F3@C prepared in Examples 1-4 and Comparative Example 1 is about 7.3wt%, and the difference in carbon content is not large, which will not affect the comparison of electrical performance test results too much.
[0144] The Na3V2(PO4)2F3@C prepared in the embodiment and comparative example 1 were subjected to scanning electron microscopy (SEM) detection. Compared with comparative example 1, the particles of Na3V2(PO4)2F3@C prepared in the embodiment were uniformly dispersed and the particle size was relatively uniform. Some SEM images are shown in FIG. Figure 6 As shown, the scales of the electron microscope images are the same, and it can be seen that the average particle size of Na3V2(PO4)2F3@C is about 1000nm; compared with Comparative Example 1, the particle size of Na3V2(PO4)2F3@C obtained in Examples 1-4 is more uniform and the distribution is more dispersed; the Na3V2(PO4)2F3@C obtained in Examples 3 and 4 has more small and medium particles and is prone to agglomeration, and compared with Examples 2-4, the particle size of Na3V2(PO4)2F3@C obtained in Example 1 is uniform and the dispersion is more uniform.
[0145] The Na3V2(PO4)2F3@C prepared in Examples 1-8 and Comparative Example 1 were added to deionized water with carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1, and then stirred in a vacuum mixer to form a stable and uniform positive electrode slurry. The positive electrode slurry was coated on aluminum foil and dried at 105°C for 6 hours to obtain a positive electrode. Metal sodium flakes of suitable size were cut as negative electrodes. 1 mol of NaPF6 was dissolved in 1L of a mixed solvent of propylene carbonate and fluoroethylene carbonate (the volume ratio of propylene carbonate and fluoroethylene carbonate was 100:6) to obtain an electrolyte. In a glove box, under an argon atmosphere, the above-mentioned positive electrode, glass fiber diaphragm, and the above-mentioned negative electrode were alternately stacked, and the above-mentioned electrolyte was injected to equip a button battery. After assembling the prepared batteries, they were left to stand at 25°C for 12 hours, and the following tests were performed on the Land-2001A battery testing system:
[0146] Each battery was subjected to charge and discharge cycle test at 1C rate current at 25°C, with a voltage range of 2V-4.5V, and the first cycle discharge specific capacity of each battery and the capacity retention rate after 50 cycles were recorded; the discharge capacity of each battery at different rates of 0.2C, 0.5C, 1C, 2C, 5C and the like as a function of the number of cycles were tested at 25°C, with a voltage range of 2V-4.5V, wherein the first cycle discharge specific capacity was equal to the ratio of the first cycle discharge capacity of each battery to the mass of the positive electrode active material in the battery, and the capacity retention rate after 50 cycles was equal to the ratio of the discharge capacity after 50 cycles to the first cycle discharge capacity, and the test results are shown in Table 1; Figure 7 and Figure 8 The charge and discharge curves of the batteries made of Na3V2(PO4)2F3@C of Examples 1-4 and Comparative Example 1 under 0.2C conditions are shown. Fig. 9 The cycle performance curves of the batteries made of Na3V2(PO4)2F3@C of Examples 1-4 and Comparative Example 1 under 1C conditions are shown. Fig.10 The rate performance curves of the batteries made of Na3V2(PO4)2F3@C of Examples 1-4 and Comparative Example 1 are shown.
[0147] Table 1 Performance test results
[0148]
[0149]
[0150] Since Na3V2(PO4)3 has a 3.4V(vs.Na + / Na) of the voltage platform. Figure 7 , Figure 8 It can be seen that the 0.2C charge and discharge curves all have a charge and discharge platform at around 3.4V. Compared with Comparative Example 1, the charge and discharge platforms of Examples 1-4 are significantly shorter, indicating that the content of Na3V2(PO4)3 impurity phase in Na3V2(PO4)2F3@C is relatively low, that is, the purity of Na3V2(PO4)2F3@C is higher; and compared with Example 2, the charge and discharge platforms of Examples 1, 3-4 are shorter, and the purity of Na3V2(PO4)2F3@C is higher.
[0151] from Fig. 9 , Fig.10As can be seen from Table 1, compared with Comparative Example 1, the Na3V2(PO4)3 impurity content in Na3V2(PO4)2F3@C prepared in Examples 1-8 is low, and the discharge specific capacity and capacity retention rate of the prepared battery are both at a high level, and the cycle performance is excellent. Among them, the discharge specific capacity of the battery prepared in Example 1 after 50 cycles at a current density of 1C is 117.5mAh / g, and the capacity retention rate is 99.0%. The discharge specific capacity at current densities of 0.2C, 0.5C, 1C, 2C and 5C is 124.0mAh / g, 121.5mAh / g, 119.1mAh / g, 115.8mAh / g and 110.0mAh / g, respectively, showing excellent performance under circulation and high rate. Therefore, the preparation method provided in the present application can prepare sodium vanadium fluorophosphate with low impurity content and high purity, and carbon-coated sodium vanadium fluorophosphate, which is beneficial to its use.
[0152] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing sodium vanadium fluorophosphate, characterized in that: include: A sodium source, a vanadium source, a phosphorus source and a fluorine source are mixed to form a first raw material, wherein the molar ratio of sodium element, vanadium element, phosphorus element and fluorine element in the first raw material is a:b:c:d, wherein a, b, c, d are real numbers greater than 0, and a, b, c, d satisfy: when a / c≤1.5, a / b<1.5, a / d<1, or when a / c≥1.5, c / b<1, c / d<2 / 3; The first raw material is processed to obtain a first precursor; The first precursor is dried and calcined to obtain sodium vanadium fluorophosphate.
2. The preparation method according to claim 1, characterized in that When a / c≤1.5, 1.36<a / b<1.5, 0.83<a / d<1, or when a / c≥1.5, 0.89<c / b<1, 0.55<c / d<2 / 3.
3. The preparation method according to claim 1, characterized in that: When a / c≤1.5, b is 2a / 3+e, d is a+3e, e>0, or when a / c≥1.5, b is c+f, d is 1.5c+3f, f>0.
4. The preparation method according to claim 3, characterized in that: When a / c≤1.5, 2.5≤a≤3.5, 0.1≤e≤0.2, or when a / c≥1.5, 1.6<c<2.4, 0.1≤f≤0.
2.
5. The preparation method according to claim 3, characterized in that: When a / c≤1.5, 12.5≤a / e≤35, or when a / c≥1.5, 8.3<c / f<23.
4.
6. The preparation method according to claim 1, characterized in that: The first raw material is processed to obtain a first precursor, including: The first raw material is treated by at least one of a solid phase method, a hydrothermal method, a sol-gel method and a spray drying method to obtain the first precursor.
7. The preparation method according to claim 1, characterized in that: The drying comprises treating at 100°C-120°C for 1h-3h; The calcination includes treating at 300° C.-400° C. for 1 h-5 h, and then treating at 600° C.-800° C. for 10 min-10 h.
8. A method for preparing carbon-coated sodium vanadium fluorophosphate, characterized in that: include: A sodium source, a vanadium source, a phosphorus source, a fluorine source and a carbon source are mixed to form a second raw material, wherein the molar ratio of the sodium element, the vanadium element, the phosphorus element and the fluorine element in the second raw material is a':b':c':d', wherein a', b', c', d' are real numbers greater than 0, and a', b', c', d' satisfy: when a' / c'≤1.5, a' / b'<1.5, a' / d'<1, or when a' / c'≥1.5, c' / b'<1, c' / d'<2 / 3; The second raw material is processed to obtain a second precursor; The second precursor is dried and calcined to obtain carbon-coated sodium vanadium fluorophosphate.
9. A battery pole piece, characterized in that: The invention comprises at least one of sodium vanadium fluorophosphate prepared by the preparation method according to any one of claims 1 to 7 and carbon-coated sodium vanadium fluorophosphate prepared by the preparation method according to claim 8.
10. A battery, characterized in that: Including the battery pole piece as described in claim 9.
11. An electrical device, characterized in that: Comprising the battery as claimed in claim 10.
Citation Information
Patent Citations
Method for preparing sodium fluorophosphate vanadium for positive pole material of sodium-ion battery
CN103022490A
Monocrystal sodium vanadyl fluorophosphate / carbon positive electrode material and preparation method and application thereof
CN115084473A
